The importance of popularizing non-conventional food plants as an alternative source of food (Research, Society and Development, 2022)
The research objective was to describe the nutritional quality of some PANC (Non-Conventional Food Plants), elucidating the importance of popularizing the consumption of PANC as a food alternative. The proposed topic is relevant because PANC have nutritional value and food potential that are still unknown to many people, in addition, food insecurity (IA) and food waste are problems that grow a lot in society. The study was conducted with data collections from secondary sources between 2012 and 2022, using a bibliographic survey based on the experiences made by the researched authors. For the literature survey we used books, primers, master's dissertations, magazines and articles on sites such as SciELO (Scientific Electronic Library Online) and INPA (National Institute for Research in Amazonas). Several PANC presented interesting compositions and nutritional potentials, however, they are not present in the population's diet due to lack of knowledge. Thus, they can benefit people's health by providing essential nutrients. Also, they can contribute to the enrichment of the diet of individuals who live with food insecurity, because they are plants that usually grow spontaneously and can be easily found anywhere.